A comercialização no desporto: gestão orientada para a promoção do clube: Relatório de estágio profissionalizante na Área Comercial e Relações Públicas do Boavista Futebol Clube - Joana Filipa Leite Gil (2018)
The following report details the professional internship held in the Commercial Area and Public Relations of Boavista Futebol Clube, more specifically, in the Commercial Department.The primary purpose of the internship was the acquisition and development of fundamental skills in performing as a sports manager, as well as for the knowledge and awareness of the circumstances that a football organization sizing such as Boavista Futebol Clube, first division team, entails.With respect to the practical duties, all the internship activities met the department's agenda that overall was based on Boavista FC promotion, through the launching of products/services and campaigns, boosting the club exposure and reliance, thus leading to an increase in sales and client satisfaction.The performed activities and tasks were framed into two key areas: administrative and marketing, with the latter being comprised by the communications and products/services field.Marketing was present, in several aspects, in the planning and development process of the department's projects. In this department, communication proved to be key to overcoming the challenges that have emerged. On the other hand, aspects such as the shortage of human and financial resources hindered the development of the department. Nevertheless, the proposed goals have been fulfilled, awaiting a future of changes.The report is structured as follows: 5 parts pertaining to 5 chapters. In the first chapter, a professional practice context is done. The second addresses all the relevant topics for the practical work, via a conceptual framework. The third chapter discusses the activities developed in the internship. In the forth, a critical analysis of the internship is considered. And lastly, the fifth chapter refers to the bibliographic references.